An Intelligent Mirror for Parenting, Supporting Aid and Personal Agent - KR, Chetan (International Journal of Computer Sciences and Engineering, 2021)
Everybody loves to be in front of the mirror at least once a day. Such a mirror can also be used as an intelligent device that can enable lot of opportunities. Intelligent mirror can help in effective parenting. Looking after child needs and keeping track of their activities like homework, eating, tuitions, sports/dance classes and others is difficult. The intelligent mirror can help by communicating child different alerts and messages, as soon as the child stands in front of mirror. Parents can keep updating instructions to mirror. Disabled people find difficulty in checking daily updates, keeping reminder systems and receiving notifications of their friends/relatives. They have to depend on someone to support all these tasks. Such people just need to be visible in front of the smart mirror and get all the required updates and notifications. Apart from these, every individual has lot of reminders, updates, and tasks to be done every day. Daily news, weather forecasts, streaming of desired videos, user interest driven advertisements need to be displayed as soon as user comes in front of mirror. The proposed intelligent mirror is developed using Raspberry Pi, two-way mirror, camera module, face recognition and server side technologies. An easy to use Android App has been developed in Kotlin to facilitate updating activity schedules, record and upload Audio messages, user to customize their interest and profile settings and view the history of schedules.